SANITASI LINGKUNGAN DESA HILIANA’A GOMO DAN PEMBELAJARAN DASAR SERTA GOTONG ROYONG MASYARAKAN DESA - Iwarman Tafonao; Dorisvan A. Hondro; Niat Hati Zebua; Junyaman Gari; Petrus Herbin Lature; Desriani waruwu; Ernalias Laia; Fonambowo Ndruru; Ukurai Laia; Mawahida Hulu; Kaminudin Telaumbanua; Fatolosa Hulu; Tatema Telambanua (Universitas Nias Raya, 2025)
Environmental sanitation is a fundamental aspect of rural community health development. This activity aims to analyze environmental sanitation conditions in Hiliana'a Gomo Village and implement improvement efforts through integrated community service programs. The methods used include direct observation of village environmental sanitation conditions, construction of supporting infrastructure in the form of trash bins and village gates, agricultural land observation to identify development potential, and implementation of basic learning programs and community cooperation activities. Observation results show that the environmental sanitation conditions in Hiliana'a Gomo Village still require improvement, especially in waste management and sanitation infrastructure. Through the construction of trash bins, the community obtained adequate facilities to manage household waste. The construction of village gates provides identity and pride for the local community. Agricultural land observation identified the potential for sustainable agricultural development that can improve community welfare. Basic learning programs provide knowledge to the community about the importance of environmental sanitation and healthy living practices. Community cooperation activities strengthen social cohesion and community participation in village development. The conclusion of this activity is the importance of a holistic approach in improving village environmental sanitation that involves active community participation, supporting infrastructure development, and strengthening community capacity through education and learning.